2020
DOI: 10.1007/s11368-020-02844-4
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition and nutrient mineralisation of leaf litter in smallholder cocoa agroforests: a comparison of organic and conventional farms in Ghana

Abstract: Purpose Although litter decomposition and nutrient release patterns have been studied in cocoa agroforestry systems in general, studies focusing on organic and conventional cocoa systems are lacking which is critical as organic farms are particularly dependent on nutrient returns from decomposing litter. Materials and methods Dynamics in leaf litter decomposition and the mineralisation of macro- and micro-nutrients in organic and conventional cocoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
1
8
0
5
Order By: Relevance
“…On the other hand, the observed results show strong evidence about the soil organisms' activity on mulching decomposition on plots where compost was applied using litterbag with 15 mm 2 mesh-type. These results agree with the previous studies that reported positive effects of organic residues management on soil organic matter dynamics [17,43,44]. These studies have reported soil improvements, and soil organisms' activity with the continuous use of compost and green manure practice in tropical and subtropical soils.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the observed results show strong evidence about the soil organisms' activity on mulching decomposition on plots where compost was applied using litterbag with 15 mm 2 mesh-type. These results agree with the previous studies that reported positive effects of organic residues management on soil organic matter dynamics [17,43,44]. These studies have reported soil improvements, and soil organisms' activity with the continuous use of compost and green manure practice in tropical and subtropical soils.…”
Section: Discussionsupporting
confidence: 92%
“…However, in agroforestry systems such as cocoa agroforestry, the management approach affects litter decomposition, which in turn, enhances or reduces nutrient supply rate through nutrient cycling (Becker et al, 2015;Fontes et al, 2014;Ofori-Frimpong et al, 2007). For example, non-synthetic agrochemical use was enough to enhance litter decomposition and nutrient mineralization in organic systems compared to conventional systems due to the presence of more well adapted decomposer communities in organic systems (Domínguez et al, 2014;Asigbaase et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the tropics, the role of litter chemistry still dominates. Litter decomposition rates in smallholder cacao agroforests in Ghana correlated with soil moisture content and pH, but not litter chemistry (Asigbaase et al 2020). In contrast, litter quality was a predominant driver of decomposition rates along a land-use gradient, including cacao agroforestry at plot/farm scale (Dawoe et al 2009;Fanin et al 2016;Hoeber et al 2020;Tanner 1981).…”
Section: Introductionmentioning
confidence: 85%
“…Reciprocal litter exchange experiments tested the combined effect of litter quality and environmental conditions on the rate of litter dry weight loss in relation to soil conditions (biota, nutrient supply, temperature, soil moisture) in forests, agricultural fields and grasslands (Asigbaase et al 2020;Hättenschwiler and Jørgensen 2010;Hoeber et al 2020;Liu et al 2010;Rachmawati et al 2019;Schilling et al 2016;Wang et al 2015). Beyond effects of litter quality and microclimate, the interaction between substrate quality and composition of the microbial community also influences litter decomposition (Fanin et al 2016;Fierer et al 2005).…”
Section: Introductionmentioning
confidence: 99%